Prediction of Solvation Free Energies of Ionic Solutes in Neutral Solvents - Kröger, Leif C; Müller, Simon; Smirnova, Irina; Leonhard, Kai (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2020)
The prediction of solvation free energies is essential for a variety of applications. Solvation free energies of neutral systems can be predicted quite accurately. The accuracy of predictions for solvation free energies of ionic solutes dissolved in neutral solvents, however, has been reported to be worse by at least 1 order of magnitude. In this study, the performance of three approaches for solvation free energy prediction of several hundred ions dissolved in neutral solvents is evaluated. The applied methods are COSMO-RS, cluster continuum model (CCM) together with COSMO-RS, and COSMO-RS-ES. It is emphasized that the reference data for model evaluation are subject to large uncertainties stemming from the impossibility to measure the so-called elusive absolute free energies of solvation of a single ion. Consequently, such uncertainty must be considered during the evaluation of prediction methods. Therefore, a straightforward approach to account for the underlying uncertainty is applied here. Hereby, it is revealed that the true performance of the method is better than what is often reported. The average absolute deviation (AAD) of COSMO-RS is calculated to be 2.3 kcal mol–1, while applying the CCM and COSMO-RS-ES each results in AADs of 2.0 kcal mol–1. This accuracy allows for qualitative assessment of solvation free energy-dependent quantities, such as reaction rate constants.